Analytic Teaching with Four Severe Language Delay Elementary Students: The Methodology without the Novels (Analytic Teaching, 1985)
Introduction:  The severe language delay (SLD) students that I see are assigned to a self-contained class of 11 students ranging in age from 5 through 10 years.  The class is taught by a speech language pathologist.  She is responsible for teaching all the academics with an emphasis on language development.  The students come to me each day for concentrated instruction in developing language skills.  Because of the various needs and ages of the students, I planned to use analytic teaching with the older four students assigned to the third, fourth, and fifth grades.